PENGARUH PEMBERIAN RANSUM KOMERSIL DENGAN PENAMBAHAN BAHAN PAKAN LOKAL TERFERMENTASI AMONIUM SULFAT DAN UREA TERHADAP BOBOT HIDUP, BOBOT KARKAS, DAN BOBOT GIBLET ITIK HIBRIDA JANTAN - Amir Husein; Rudy Sutrisna; Dian Septinova (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This research aimed to know the influence of giving a commercial ration with addition of local feed fermented with ammonium sulphate and urea and to find out the best ration on live weight, carcass weight, and giblet weight of male hybrid ducks. This research was carried out in July 2018–August 2018 in the cage of ducks, Department of Animal Husbandry, Faculty of Agriculture, Lampung University. Research material used consisted of 40 male hybrid ducks. This study used a Completely Randomized Design (CRD). Data was analysed using analysis of variance at 5% level of significance. The results showed that there was no different effect of treatments on live weight (1,552–1,717 g / duck), carcass weight (805,6–1.016 g / duck), and giblet weight (106.8–118.45 g /duck) of male hybrid ducks. Keywords: Carcass weight, Giblet weight, Live weight, Male hybrid duck.